Análise de uma experiência de ensino de termodinâmica baseada em umaabordagem CTS (Ciência, Tecnologia e Sociedade) em uma escola técnicafederal de Minas Gerais - Alfredo Melk de Carvalho (2017)
The research described here had its origin in the anxieties experienced during a development experience of a teaching sequence of thermodynamics with STS (Science, Technology and Society) approach in a federal teaching institution, in this case, a technical high school. We'vedeveloped the contents of thermodynamics based in the combustion engine operation and analyze the issues of urban mobility and pollution generated by it. We work with physics content with students of the 2nd year of High School. The sequence was developed in 2011, 2012, 2014and 2016, considering that at the first two years I was present in its implementation in my classes, when I worked at the institution. With this work we analyze the development of a sequence with the objective of endorsing or not the use of this IS (Instructional Sequence) with CTS approach as a proposal of the teaching of physics. The CTS approach aims to implement in the science curricula of elements of technology and society, evidencing the relation of this triad (science-technology-society). One of their goals is to develop students' values and knowledge that allows them to act in a critical form in the society when questions related to science and technology emerges. Being a technical training school, where teaching is linked to a professional training, the use of the CTS approach is also justified by evidenciating a greater linkage of teaching to the world of work by relating science and technology to their effects in society. We tried to identify and analyze how surgical stresses during the implementation of the sequence, in order to validate or not of its use. We used as source of data: interviews with the students and teachers, who participated in the project, as well as the data from a questionnaire, answered by the students, about this sequence evaluation. Our analysis is supported by the theoretical-methodological reference linked to the historical-cultural approach, through the concepts and theories of Lev Vygotsky and Mikhail Bakhtin. We believe that by means of this data analysis and dialoguing with the literature about this subject, we can have a better knowledge of this experience by identifying the emergent tensions in the development of this approach CTS in science teaching, in this case, in the teaching of Physics. We also intend, from the evaluation of this project, to produce teaching materials and guidelines for the application of this proposal in the classroom.